Effectiveness Infant Massage Provided by Mother on Weight Gain Among Premature Infants: A Systematic Review - Kusnul Hasanah; Endah Dessirya; Yeni Rustina; Robiyatul Adawiyah; Mega Hasanul Huda (GLOBAL HEALTH SCIENCE GROUP, 2025)
Premature birth poses significant health challenges with implications of low birth weight in infants. Infant massage intervention by mothers shows potential in enhancing weight gain in premature infants and improving their neurological and emotional development. This study aims to evaluate the effectiveness of such interventions in promoting holistic growth in premature infants.Objective: This article aims to investigate the effectiveness of infant massage intervention involving mothers in enhancing weight gain in premature infants.Methods: This study employed a systematic review method. A search in the PubMed, Science Direct, Sage Journals, Scopus, Taylor & Francis, Proquest, Clinical Key to retrieve randomized controlled trial of premature infants receiving massage therapy by mother impact of weight gain on infant premature. The registration number was CRD42024622719.Results: Of 883 record article retrieved, 5 RCTs with 406 participans were included. Literature studies indicate that infant massage involving mothers has beneficial effects on premature infants, such as calorie intake, head circumference, body length, nerve development, length of stay (LOS), and sepsis incidence in premature infants. Massage therapy by the baby's mother also did not have any side effects or cause complaints, and no secondary effects were found.Conclusion: Infant massage by mothers is an effective intervention in enhancing weight gain in premature infants. Involving parents in the care of premature infants through interventions like this can provide significant benefits for the well-being and development of premature infants.